2018
DOI: 10.1038/s41598-018-29191-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of Spin-Wave Propagation using Magnetisation Gradients

Abstract: We report that in an in-plane magnetised magnetic film the in-plane direction of a propagating spin wave can be changed by up to 90 degrees using an externally induced magnetic gradient field. We have achieved this result using a reconfigurable, laser-induced magnetisation gradient created in a conversion area, in which the backward volume and surface spin-wave modes coexist at the same frequency. Shape and orientation of the gradient control the conversion efficiency. Experimental data and numerical calculati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 47 publications
0
38
0
1
Order By: Relevance
“…Prerequisites for that are well-investigated and understood properties of the particles and thus the possibility to control their behavior. [2][3][4] The scope of our research is the investigation of magnetization dynamics as it provides an opportunity for highly advanced magnetic memory and logic devices. [5][6][7] Magnons or spin-waves, being the elementary excitations of coupled spin systems in solids, have been widely investigated in thin films, [8][9][10] nanostructured multilayers, 11 magnonic crystals, [12][13][14][15] and magnonic waveguides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prerequisites for that are well-investigated and understood properties of the particles and thus the possibility to control their behavior. [2][3][4] The scope of our research is the investigation of magnetization dynamics as it provides an opportunity for highly advanced magnetic memory and logic devices. [5][6][7] Magnons or spin-waves, being the elementary excitations of coupled spin systems in solids, have been widely investigated in thin films, [8][9][10] nanostructured multilayers, 11 magnonic crystals, [12][13][14][15] and magnonic waveguides.…”
mentioning
confidence: 99%
“…[26][27][28][29] In most of the cases, spin-waves are investigated using a nonuniform excitation of the structure. 2,4,10,12 When the uniform excitation field is applied to the specimen, it is also possible to excite spin-waves, but only standing spin-waves are expected. 30 A standing spin-wave implies that its nodes remain at the same position in space over the time.…”
mentioning
confidence: 99%
“…To change the wave number and thus the index for the given wave frequency, we need to change the dispersion relation by varying one of the bulk material parameters, or film thickness [11][12][13][14][15] . We then need to choose an isotropic dispersion relation that enables a large change in k, and thus n. This requirement is satisfied in the dipolar-dominated regime, in the forward-volume geometry, where the magnetization is directed normal to the film plane.…”
Section: Theory Of Spin Wave Steering Lensesmentioning
confidence: 99%
“…However, these waveguides may suffer from losses/scattering in bends, and usually have a large spatial footprint. An alternative solution is to steer spin waves via a graded refractive index [11][12][13][14] , which smoothly alters the wave trajectory with minimal reflections 15 . To achieve a graded index for spin waves, one must gradually change a magnonic parameter on a length scale much smaller than the wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…A main aspect of this confinement at relatively low frequencies is the formation of a caustic beam [10][11][12]. Additionally, it has been shown that refractive spin-wave optics can be realized [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%